Media Framing and the Construction of Conflict Narratives in the Digital Age - Assan Halima Kofoworola (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2026)
The paper examines the challenges of regulations, ethical issues, digital disinformation and algorithmic influence of social media on public discourse. It established that media literacy, professional ethics and regulation are the solutions to the problems that will make the media serve as peace makers in conflict and national unity in Nigeria. Conflict sensitive reporting as a tool for peace journalism was concluded as the best medium to avoid the tensions that arise from false information and biased reporting. This proactive approach not only addresses the immediate challenges but also lays the groundwork for a more resilient society. This paper discusses the Farmer herder, tribal and religious crisis, protest movement (EndSARS protest). Based on Framing Theory, and Agenda-Setting Theory, the paper explained that Nigeria media serve as a double-edged sword as they are both war mongers and peace makers. Sensible reports and factual information reduce conflicts and tension arising from fake news and disinformation. It concludes that media literacy, professional ethics and regulation are the solutions to the problems that will make the media serve as peace makers in conflict and national unity in Nigeria. Drawing from the theoretical postulation of Framing Theory, and Agenda-setting theories, the paper argues that Nigeria’s media acts as both an instigator and a peacemaker that connotes the functionality of two sides of one coin.